Evaluating dexmedetomidine in mitigating emergence agitation and perioperative complications in pediatric tonsillectomy and/or adenoidectomy: a systematic review and meta-analysis - He, Jihong; Lian, Xianghong; Luo, Ting (Frontiers in Pharmacology, 2025)
BackgroundPerioperative complications and emergence agitation (EA) are common after pediatric tonsillectomy and/or adenoidectomy (T&A), and may be influenced by the use of preoperative sedatives. The effectiveness of dexmedetomidine (Dex) in minimizing these risks is still debated.MethodsWe searched EMBASE, PubMed, and the Cochrane Library for randomized controlled trials (RCTs) assessing the safety and effectiveness of Dex in pediatric T&A, with comparisons made against placebo and/or alternative comparators. The search included studies published before March 2025. Retrieved data included the incidence of EA, the percentage (%) of cases requiring rescue analgesics, and perioperative complications, such as hypotension and bradycardia, and perioperative respiratory adverse events (PRAEs). The meta-analysis was performed using RevMan 5.3.ResultsThirty-six RCTs including 3,773 children were included. Compared with placebo, benzodiazepines, and opioids, Dex significantly reduced the occurrence of EA [OR = 0.23, 95% CI (0.16, 0.32), I2 = 44%] [OR = 0.51, 95% CI (0.28, 0.93), I2 = 44%] [OR = 0.19, 95% CI (0.09, 0.39), I2 = 0%] (P < 0.05). Subgroup analysis of delivery methods, timing, and dosage (Dex ≥0.5 μg/kg) indicated that Dex significantly decreased the incidence of EA (P < 0.05). Furthermore, compared with placebo and benzodiazepines, Dex markedly decreased the incidence of patients necessitating rescue analgesia, while no statistically significant difference was noted versus opioids. Dex also significantly decreased the incidence of PRAEs (oxygen saturation (%) and laryngospasm) [OR = 0.41, 95% CI (0.25, 0.69), I2 = 0%] [OR = 0.38, 95% CI (0.19, 0.78), I2 = 0%] (P < 0.05) However, there was no significant difference in the incidence of hypotension or bradycardia [OR = 2.28, 95% CI (0.99, 5.23), I2 = 0%, P = 0.05] [OR = 2.00, 95% CI (1.00, 3.98), I2 = 2%, P = 0.05]. Finally, recovery time did not differ significantly between the Dex and control groups.ConclusionDex may mitigate EA and perioperative complications while enhancing recovery quality following T&A in pediatric patients.